Analysis of Alcohol Content in Anaerobic Fermentation of Watermelon (Citrullus lanatus) and Orange (Citrus sinesis) using Fermipan - Amanah, Firda; Andika, M. Reisa; Hapsari, Lativa Restu; Pujiati; Wijayanti, Dinda Ayu; Rahayu, Triastuti (Urecol Journal. Part C: Health Sciences, 2023)
Fermentation is a process of chemical changes in organic substrates through enzymes obtained by microorganisms which is an anaerobic deassimilation of organic compounds and is caused by the activity of microorganisms. This study aims to determine the alcohol content in different formulations of fermipan addition used in orange and watermelon liquids. The research design method used in this study is a Complete Randomized Design (CRD) consisting of two factors. The first factor is the type of substrate (S): watermelon (S1) and orange (S2), while the second factor is the concentration of yeast/Fermipan: 0% (R1), 1% (R2), 2% (R3). Data analysis was done descriptively quantitative and descriptive qualitative. The results showed that alcohol content with orange substrate was higher than watermelon. Other alcohol fermentation activities such as pH, CO2 and H2O also corroborate the data that the orange substrate is more active than the watermelon substrate. More yeast concentration (up to 2%) resulted in higher alcohol content and alcoholic fermentation activity.